Improving Pedagogic Competence Of Non-Education Teachers In Preparing Lesson Plan Through Supervision Academic Of The Headmaster - Deli Rahyuni (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Educational reform is not enough with changes in the curriculum sector, both the structure and the writing procedure. Updating the curriculum will be more meaningful if followed by changes in learning practices inside and outside the classroom. The success of curriculum implementation is strongly influenced by the ability of teachers to apply and actualize the curriculum. Not infrequently the failure of curriculum implementation is caused by the lack of knowledge, skills and ability of teachers in understanding the tasks that must be implemented. This means that the teacher as the executor of the learning activities becomes the key to the implementation of the curriculum in the school.